For My People - Walker, Margaret (Yale University Press, 2019)
An exploration of race and heritage, For My People is the first book by poet and novelist Margaret Walker (1915-1998) and the 41st volume of the Yale Series of Younger Poets.
Keywords: African Americans -- Poetry.; Noirs américains -- Poésie.; POETRY -- American -- African American.; African Americans; Poetry